The Development of Android-Based Learning Media for Basic Accounting Subjects for Class X AKL at Al Ikhlas Vocational High School, Pangkalan Susu, Langkat Regency - Trysanti Kisria Darsih; Elfi Lailan Syamita Lubis (Budapest International Research and Critics University, 2021)
This study aims to develop an Android-based learning application and compare student learning outcomes before and after using Android-based learning media in Basic Accounting subjects for class X AKL at Al Ikhlas Vocational High School Pangkalan Susu, Langkat Regency. The type of this research is the Borg & Gall R & D model. The stages carried out in the development of this media are the research and information gathering stage, the planning stage, the initial product development stage, the initial field test stage, the first stage of product analysis and revision stage, the field trial stage. Product II revision stage, and product refinement and implementation stage. The results showed that this android-based learning is valid based on the validation results of media experts reaching a percentage of 80% in the Good category, the results of material expert validation reaching a percentage of 76.5% in the Good category and the validation results of learning experts reaching a percentage of 82.7% in the Good category. Thus the android-based learning media developed is feasible to use. The increase in learning outcomes is shown by data analysis from pretest and posttest from the results of the T test which was carried out using the Pired Samples Test with a 95% truth level obtained a significance result of 0.000 <0.05, so there is a significant difference in student learning outcomes between before and after using android-based learning media.